Loan ko 'to assessing the prevalence and productivity of the informal credit market - Bernardo, Ivan Cenon V. (School of Economics, University of the Philippines Diliman, 2018)
According to the 2014 Consumer Finance Survey of the Bangko Sentral ng Pilipinas (BSP), the informal credit market serves as the main source of financing for Filipino households, with 70 percent of households reporting to have some form of informal loan. This paper aims to determine the characteristics of informal loan borrowers and whether such informal credit is being allocated for productive purposes. By employing a multinomial logistic regression model to simulate the decision_making process of a borrower, we found that family size, educational attainment, location of residence, income, and property ownership are significant predictors of the likelihood of whether one will avail of an informal loan. Further, we found that informal loans are found to be utilized for investments in physical capital rather than other types of consumption or investment purposes. These findings imply that interventions of both the BSP and other government agencies to improve accessibility of formal credit and government loans will have long_term implications for inclusive economic growth.